2015
DOI: 10.4028/www.scientific.net/amm.747.294
|View full text |Cite
|
Sign up to set email alerts
|

Fish Distribution and Composition of Kelantan River Systems, Kelantan, Malaysia

Abstract: Fish from three major rivers namely Pengkalan Chepa, Kelantan, and Galas rivers in Kelantan, Malaysia was caught using gill-nets with separate mesh sizes of 1, 2, 3, and 4 inches, respectively. There were 170 fish collected from the PCR systems, which represented 18 families and 21 species (2008-2009). The most common fishes, based on total fish captured, were Ikan duri (Arius maculatus) and Puyu (Anabas testudineus). A total of 245 individual fish were collected from KR (2010-2012) which comprised of 7 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…Farombi et al, (2007) observed similar trends in the liver and kidney C. gariepinus from the Ogun River. Cd concentrations in fish were higher than acceptable limits, and Cd concentrations in this study were similar to those reported by Hashim et al (2014) who observed concentrations in fish higher than recommended permissible limits in a study conducted in the Keratan River, Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…Farombi et al, (2007) observed similar trends in the liver and kidney C. gariepinus from the Ogun River. Cd concentrations in fish were higher than acceptable limits, and Cd concentrations in this study were similar to those reported by Hashim et al (2014) who observed concentrations in fish higher than recommended permissible limits in a study conducted in the Keratan River, Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…Farombi et al, (2007) observed similar trends in the liver and kidney C. gariepinus from the Ogun River. Cd concentrations in fish were higher than acceptable limits, and Cd concentrations in this study were similar to those reported by Hashim et al (2014) who observed concentrations in fish higher than recommended permissible limits in a study conducted in the Keratan River, Malaysia. Cadmium can be introduced into water bodies using cadmium-rich fertilizers, septic agents and pesticides, which can affect the kidneys and cause chronic toxicities such as kidney damage, reduced fertility and liver dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…On the east coast of Malaysia, the Tor species have been reported to inhabit Galas, Nenggiri, and Lebir Rivers that meet to form the Kelantan River in the state of Kelantan. However, a study in 2015 described the failure to capture the Tor species, especially T. tambroides in the Kelantan River [ 45 , 46 ]. From 2016 to date, there no study has been conducted to validate the disappearance of Tor species in the Kelantan River.…”
Section: Geographical Distribution Of Tor Species In the Se Asian Regionmentioning
confidence: 99%